2016
DOI: 10.3390/rs8010044
|View full text |Cite
|
Sign up to set email alerts
|

Extent and Area of Swidden in Montane Mainland Southeast Asia: Estimation by Multi-Step Thresholds with Landsat-8 OLI Data

Abstract: Information on the distribution, area and extent of swidden agriculture landscape is necessary for implementing the program of Reducing Emissions from Deforestation and Forest Degradation (REDD), biodiversity conservation and local livelihood improvement. To our knowledge, explicit spatial maps and accurate area data on swidden agriculture remain surprisingly lacking. However, this traditional farming practice has been transforming into other profit-driven land use, like tree plantations and permanent cash agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 46 publications
1
25
0
Order By: Relevance
“…On the basis of previous literature (Li et al, ; Ziegler et al, ) and our field investigations between 2013 and 2019, the burning of sun‐ and air‐dried vegetation of swidden agriculture from February to April during the dry season is widely distributed in MSEA and causes substantial existence of active fires. Thus, we therefore believe that active fires in MSEA are significantly related with traditional slash‐and‐burn practices during the dry season, especially in March and April (Li & Feng, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of previous literature (Li et al, ; Ziegler et al, ) and our field investigations between 2013 and 2019, the burning of sun‐ and air‐dried vegetation of swidden agriculture from February to April during the dry season is widely distributed in MSEA and causes substantial existence of active fires. Thus, we therefore believe that active fires in MSEA are significantly related with traditional slash‐and‐burn practices during the dry season, especially in March and April (Li & Feng, ).…”
Section: Resultsmentioning
confidence: 99%
“…Our hourly statistical results for the distribution of occurrence frequency of active fires in MSEA were in accordance with the fact that the swiddening practice has been comparatively concentrated between 12:30 and 14:30 ZT during March and April (MĂŒller et al, ). Not coincidentally, some earlier research has shown that active fires in MSEA are usually caused by the swidden‐related burning in the uplands and the burning of agriculture residues in the plain area (Li & Feng, ; Liao et al, ; Shi & Yamaguchi, ; Vadrevu & Justice, ). As a result, this important conclusion comprehensively and robustly validates again the fact that the majority of active fires in MSEA are triggered by swidden agriculture of local farmers (Li, Feng, Xiao, et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…forest cover, there are hardly any spatially explicit datasets covering wide areas that could serve to independently assess the functions, uses and other socio-economic dimensions implicit to the characteristic management type of a landscape. Despite these constraints, we provide alternatives to evaluate the land systems classification of this study by discussing the uncertainties of the input data, the impacts of spatial resolution and compare the classification result to a national mapping of mosaics by Messerli et al 2009 and to remote sensing studies on shifting cultivation by Hurni et al, (2012) and Li & Feng (2016). Finally, we zoom in on two areas to see in how far the classification matches with examples of case study research on shifting cultivation and the agrarian transition.…”
Section: Accuracy and Validitymentioning
confidence: 99%
“…Land use or fire history assessments can be obtained from archived aerial photographs, satellite images or official records [7][8][9][10]. The slash-and-burn farming shows a specific pattern of regular fire cycles (starting with slashing and followed with ground fire), which is different from the natural forest fires [11].…”
Section: Introductionmentioning
confidence: 99%